Pengaruh Pemanfaatan Semen Grouting StrongGrout G70 Sebagai Filler terhadap Karakteristik dan Durabilitas Campuran AC-WC - Rezki Muhammad Suharto Hartawan Nurdin; Hanafi Ashad; Andi Alifuddin (Universitas Batanghari Jambi, 2026)
Transportation plays an important role in supporting mobility which is highly dependent on the quality of road pavement. Premature damage to the asphalt surface layer often occurs due to increased traffic volume, excessive loads, and low water resistance. This study aims to analyze the effect of using StrongGrout G70 grouting cement as a filler on the Marshall characteristics and durability of the Asphalt Concrete–Wearing Course (AC-WC) mixture, as well as determining the optimum filler content. The research method uses an experimental approach with variations in StrongGrout G70 content of 0%, 0.5%, 1%, 1.5%, and 2% of the total aggregate weight. The mixture characteristics were tested using the Marshall method, while durability was evaluated through the Residual Strength Index (RSI), First Durability Index (FDI), and Second Durability Index (IDK), according to the 2025 General Bina Marga Specifications. The test results showed that stability increased from 1351.94 kg (0%) to 1615.55 kg (2%), flow decreased from 3.10 mm to 2.50 mm, VIM decreased from 4.28% to 3.21%, VFA increased from 73.84% to 79.10%, VMA decreased from 16.20% to 15.26%, and Marshall Quotient increased from 439.26 kg/mm to 648.64 kg/mm. In durability, the IKS variation of 2% reached 96.70% (24 hours), 94.35% (36 hours), 91.54% (48 hours), 88.94% (60 hours), and 83.54% (72 hours), higher than 0% which was only 76.95% at 72 hours. The IDP value of 2% ranged from 0.14%–0.23% and the IDK Sa decreased from 98.92% to 92.43% with a strength loss of 1.08%–7.57%. The results showed that the use of StrongGrout G70 at 2% provided the best performance on the stability and durability of the AC-WC mixture.